Jejunal limb obstruction by a tumor thrombus from pancreatic metastasis of renal cell carcinoma: a case report - Shinya Sakamoto; Masaru Matsumura; Keigo Tani; Satoshi Nemoto; Kazuhito Tsuchida; Fumitaka Koga; Yasuji Seyama (Surgical Case Reports, 2021)
Abstract Background Renal cell carcinoma (RCC) is a primary tumor with the highest frequency of pancreatic metastasis. Although surgical resection can improve the prognosis of some patients with pancreatic metastasis of RCC (PM-RCC), the role of palliative surgery remains unclear. Herein, we described a case of jejunal limb occlusion caused by a tumor thrombus arising from a PM-RCC which was treated by surgical resection. Case presentation A 75-year-old, male patient with metastatic RCC was admitted to our hospital with new-onset dysphagia and weight loss. Twenty years earlier he underwent a right nephrectomy with an adrenalectomy for the first surgical resection of RCC, and 12 years ago he underwent a left partial nephrectomy for metachronous primary RCC. Nine years later, multiple pancreatic metastases were detected. After discontinuing interferon therapy, he was followed up at his request without anticancer treatment. Multiple, pulmonary metastases developed 3 years ago, and resection of a brain metastasis was performed 6 months ago. He had also undergone a total gastrectomy with Roux-en Y reconstruction and splenectomy for gastric cancer 23 years ago. Computed tomography revealed a metastatic lesion in the pancreatic tail extending into the jejunal limb, which was obstructed by a tumor thrombus. Jejunal limb resection was performed concomitantly with a distal pancreatectomy as palliative surgery. The jejunal limb remnant was approximately 30 cm long and was re-anastomosed to the esophagus using a circular stapler. Blood perfusion at the anastomotic site was confirmed by indocyanine green fluorescence imaging. He was discharged on postoperative day 24 and was followed in the outpatient clinic. He achieved sufficient oral intake at 8 months postoperatively. Conclusions PM-RCC can invade the gastrointestinal tract and cause tumor thrombus formation resulting in bowel occlusion requiring surgical intervention.